Towards a feminist trade unionism? An analysis of kelly’s fight - Castellano Díaz, Julia (Papeles de Europa, 2023)
Feminist unionism has gained strength in recent years, with the emergence of multiple alternative associations to traditional class unions, such as Las Kellys. The following research, based on a Feminist Political Economy approach, verifies the influence of the capitalist-patriarchal system in the configuration of gender-biased union relations through the sexual division of labor in coexistence with the historical construction of a masculine and industrial union archetype. As a result, autonomous feminist workers’ organizations have emerged to challenge the established order and revitalize Spanish trade unionism and labor movement through a class, feminist and inclusive trade unionism, as Las Kellys, living example of this phenomenon.